Traumatic exposure and posttraumatic symptoms for train drivers involved in railway incidents - Doroga, Corina; Băban, Adriana (Medicine and Pharmacy Reports, 2013)
Aims. International research highlights the occupational risk of train drivers of being exposed to work related traumatic incidents and subsequently developing posttraumatic symptoms or other comorbid dysfunctions. Participants and methods. The article focuses on investigating the effects of repeated traumatic exposure on posttraumatic reactions in a sample of 193 Romanian train drivers. We used the Impact of Event Scale-Revised (IES-R) to retrospectively evaluate symptoms of Posttraumatic Stress Disorder (PTSD), The General Health Questionnaire to investigate related mental health symptoms, and a demographic questionnaire to assess contextual factors like frequency or severity of exposure. Results. Sample reports of exposure to PUT (“person under train”) incidents were high. An interesting finding was that train drivers exposed to just one or two PUT incidents reported significantly more posttraumatic symptoms than train drivers with more PUT experiences, accounting for a habituation effect of repeated traumatic exposure. Conclusions. Reported posttraumatic reactions to PUT incidents and influencing factors provide evidence recommending systematic screening of train drivers for posttraumatic symptoms, general emotional distress and further elaborating prevention and treatment strategies for specific risk categories of these professionals.